IKAROS levels are associated with antigen escape in CD19- and CD22-targeted therapies for B-cell malignancies - Pablo Domizi; Jolanda Sarno; Astraea Jager; Milton Merchant; Kaithlen Zen B. Pacheco; Sean A. Yamada-Hunter; Maria Caterina Rotiroti; Yuxuan Liu; Reema Baskar; Warren D. Reynolds; Brian J. Sworder; Bita Sahaf; et al. (Nature Communications)
Abstract Antigen escape relapse is a major challenge in targeted immunotherapies, including CD19- and CD22-directed chimeric antigen receptor (CAR) T-cell for B-cell acute lymphoblastic leukemia (B-ALL). To identify tumor-intrinsic factors driving antigen loss, we perform single-cell analyses on 61 B-ALL patient samples treated with CAR T cells. Here we show that low levels of IKAROS in pro-B-like B-ALL cells before CAR T treatment correlate with antigen escape. IKAROSlow B-ALL cells undergo epigenetic and transcriptional changes that diminish B-cell identity, making them resemble progenitor cells. This shift leads to reduced CD19 and CD22 surface expression. We demonstrate that CD19 and CD22 expression is IKAROS dose-dependent and reversible. Furthermore, IKAROSlow cells exhibit higher resistance to CD19- and CD22-targeted therapies. These findings establish a role for IKAROS as a regulator of antigens targeted by widely used immunotherapies and in the risk of antigen escape relapse, identifying it as a potential prognostic target.